Daur ʻIlm al-Lugah an-Nafsī fī Taʻlīm al-Lugah al-ʻArabiyyah li Gair an-Nāṭiqīn Bihā - Imam Wahyudi; Zainuri Zainuri (INAIFAS PRESS, 2021)
Learning is a unit consisting of various factors that support each other. In learning Arabic, it is not only teacher factors and Arabic language material that must be considered, students as second language learners also need attention for the success of learning. The purpose of this article was to describe the role of psycholinguistics in learning Arabic for non-native speakers. Researchers used literature review to extract data from various sources. From the data obtained, it was known that the role of psycholinguistics in learning Arabic makes teachers able to understand the processes that occur in students when they listen, speak, read, or write. Psycholinguistics as an applied science between psychology and linguistics can be used to understand the behavior of second language learners, language acquisition, and language production and the processes that occur in it.